Simply effective : how to cut through complexity in your organization and get things done - Ashkenas, Ronald N. (Ascent Audio, 2023)
The level of complexity in most organizations today is staggering-and it's only getting worse. There are so many choices to be made, people to involve, processes to manage, and facts to analyze, it's impossible to get things done. And in today's hypercompetitive world, that can be fatal. Yet complexity doesn't happen on its own. Managers unwittingly create it, often through well-intended decisions. In Simply Effective, Ron Ashkenas provides a playbook for regaining control, focused on the four major causes of complexity: constant changes in organizational structures, proliferation of products and services, evolution of business processes, and time-wasting managerial behaviors. The author provides a diagnostic for identifying how these causes of complexity are affecting your organization-and presents practical tactics for combating each one. Ashkenas also explains how to craft a strategy that will make simplification an ongoing driver of your company's success-no matter where you work in your organization. Abundant examples from companies like ConAgra Foods, GE, Cisco, Zurich Financial Services, and Johnson & Johnson illuminate his points.